Development of Fukado Learning Media on Mathematics Content of Space Building Materials on The Improvement of Student Results Class VI at SD Negeri Sadeng 01 Semarang City - Farid, Nizar; Nugraheni, Nursiwi (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The purpose of this study was to develop Fukado media with Borg and Gall's development theory through 10 stages of development so that the developed media can be used to achieve learning objectives, namely improving student learning outcomes. The research subjects used 6th-grade students at SD Negeri Sadeng 01 Semarang City with 27 students. Augmented reality is one of the media that can help with learning. The development of this media is done by analyzing problems, designing media, media validated by experts, and testing on learning. The effectiveness of this learning media is seen with assessment instruments on validity, effectiveness, and practicality. Media development that has gone through various stages of development is declared successful with a level of validity of media, material, and language of 88%, 95%, and 91% respectively, The effectiveness of the media can be seen from the increase in learning outcomes in mathematics learning with the difference in the average student score reaching 15 from the original 61 to 76 obtained from trials with pretest and posttest.